ChemInform Abstract: First Report of Multiple Metal Ions Containing Glass—Ceramic Material as a Heterogeneous Ditopic Catalyst for the Chromatography Free Synthesis of 2‐Amino‐3, 5‐dicarbonitrile‐6‐arylthio‐pyridines in Water. Issue 49 (December 2015) - Manna, Priyabrata; Maiti, P. K.
Abstract: The title glass‐ceramic material is synthesized and utilized as catalyst for the three‐component condensation of aldehydes, thiols, and malononitrile.